Emotional health: Understanding and definition - I. B. Nazarova; S. V. Lyalikova (RUDN journal of Sociology)
The concept of “emotional health” is actively discussed in the scientific community and is subject to various interpretations; the lack of its clear definition leads to the use of synonyms such as “emotional well-being” or “mental health” which do not fully reflect the features of the phenomenon. The difficulty in defining emotional health is determined by its connection with the individual mental, psychological and social well-being. Thus, emotional health is assessed with such indicators as stress levels, depression, life satisfaction, happiness indices, etc. The authors emphasize the importance of emotional competence for achieving stable emotional-positive well-being and successful functioning in society. The article presents the results of the qualitative study of various aspects of emotional health as interpreted by representatives of different social-demographic groups: respondents expressed their understanding of emotional health through other types of health, often linking it to psychological, mental or physical health. Emotional health reflects the general emotional state and is related to the ability to experience and manage various emotions, to correctly respond to current events. Emotional health is determined by subjective value perception of one’s condition, is interpreted as a state or a process, activity or passivity, and can be extrapolated to oneself or others. Emotional health is complexly organized and associated with feelings, mood, emotions, experiences; it is not a single fleeting state but rather a combination of one’s states in the past, present and future. Studies of emotional health indicate its complexity and multi-faceted nature, which means the need for an integrative approach for its thorough empirical study and full understanding of its role in human life.